The prevalence of the stylohyoid ligament ossification in Surabaya, Indonesia: an incidental finding study in panoramic radiographs - Savitri, Yunita; Wahyuni, Otty Ratna; Zulfikar, Cut Zahra (Majalah Kedokteran Gigi Indonesia, 2025)
Stylohyoid ligament ossification is a growth disorder that is often detected as an incidental finding on panoramic radiography. Its etiology and pathogenesis are still not fully understood. Eagle's Syndrome is related to stylohyoid ligament ossification, but this syndrome is often misdiagnosed or even undiagnosed so that the patients experience losses due to undergoing various unnecessary treatments. The appearance of stylohyoid ligament ossification on panoramic radiography can help to confirm the diagnosis of Eagle's Syndrome. Until now there has been no research regarding stylohyoid ligament ossification at RSGMP UNAIR. This study amied  to determine the incidence of stylohyoid ligament ossification that is observed through panoramic radiography at RSGMP UNAIR. This research is a descriptive observational study. The data used is secondary data from soft file panoramic radiographs of RSGMP UNAIR patients in the period May 2019-May 2023 which is in accordance with the sample inclusion criteria, as well as reading results by a dental radiology specialist. The data was then grouped based on gender, age, and morphology (unilateral/bilateral) and analyzed using the Cohen's Kappa Coefficient reliability statistical test. The results showed that 416 patients (9.09%) experienced stylohyoid ligament ossification. The highest distribution occurred in female with 260 patients (62.5%), the 25-64 years age group with 274 patients (65.86%) and the bilateral type with 341 patients (82%). From this study, the distribution data of stylohyoid ligament ossification based on gender, age, and morphology (unilateral/bilateral) were obtained.